Extrapleural pneumonectomy (EPP) vs. pleurectomy decortication (P/D) - BATIREL, HASAN FEVZİ (AME PUBL CO, 2017)
Surgical techniques for treatment of malignant pleural mesothelioma (MPM) have improved over the decades. The main surgical principle was accepted as macroscopic complete resection. This principle was achieved with extrapleural pneumonectomy (EPP) and extended pleurectomy/decortication (P/D). Mortality and morbidity are higher following EPP with supraventricular arrhythmias, pulmonary embolism, bronchopleural fistula and pulmonary failure being the most common, while prolonged air leak is frequent following P/D. Completion of multimodality treatment was also shown to be a prognostic factor. Many different neoadjuvant and adjuvant protocols were applied with limited effect on prognosis. While locoregional recurrence is more common following P/D, EPP patients typically recur in contralateral hemithorax and abdomen. Hemithoracic radiation following EPP was the only effective technique shown to decrease locoregional recurrence. However, neither surgical technique (EPP vs. P/D), nor types of multimodality treatment protocols were found to be prognostic in MPM. Epithelioid histology, metastasis to extrapleural lymph nodes and completion of multimodality treatment were prognostic in most of the series. In conclusion, based on the current evidence, the choice of a less morbid and mortal procedure (P/D) seems to be the logical choice in the treatment of MPM.
Keywords: Extrapleural pneumonectomy (EPP); pleurectomy/decortication (P/D); malignant pleural mesothelioma (MPM); MALIGNANT PLEURAL MESOTHELIOMA; LONG-TERM SURVIVAL; PHASE-II; HEMITHORACIC RADIATION; MULTIMODALITY THERAPY; TRIMODALITY THERAPY; RADICAL SURGERY; MANAGEMENT; PLEURECTOMY/DECORTICATION; CHEMOTHERAPY